2015
DOI: 10.1007/s10803-015-2551-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Faux Pas Detection in Adult Autism Reflect Differences in Social Cognition or Decision-Making Abilities?

Abstract: 43 typically-developed adults and 35 adults with ASD performed a cartoon faux pas test. Adults with ASD apparently over-detected faux pas despite good comprehension abilities, and were generally slower at responding. Signal detection analysis demonstrated that the ASD participants had significantly greater difficulty detecting whether a cartoon depicted a faux pas and showed a liberal response bias. Test item analysis demonstrated that the ASD group were not in agreement with a reference control group (n = 69)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 22 publications
6
32
0
1
Order By: Relevance
“…Poorer performance of ASD adults compared to NC on cognitive ToM, affective ToM and interpersonal understanding of social norms supports previous findings (Baron -Cohen, Wheelwright, Hill, et al, 2001;Castelli et al, 2002;Golan et al, 2006;Murray et al, 2017;Thi ebaut et al, 2016;Zalla et al, 2009). Although the ESCoT showed good sensitivity on all subtests, the finding that ASD adults showed impaired intrapersonal understanding of social norm is somewhat in contrast to our prediction and previous findings of intact performance (Baez et al, 2012;Gleichgerrcht et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Poorer performance of ASD adults compared to NC on cognitive ToM, affective ToM and interpersonal understanding of social norms supports previous findings (Baron -Cohen, Wheelwright, Hill, et al, 2001;Castelli et al, 2002;Golan et al, 2006;Murray et al, 2017;Thi ebaut et al, 2016;Zalla et al, 2009). Although the ESCoT showed good sensitivity on all subtests, the finding that ASD adults showed impaired intrapersonal understanding of social norm is somewhat in contrast to our prediction and previous findings of intact performance (Baez et al, 2012;Gleichgerrcht et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Violating a social norm can be detrimental to existing relationships or opportunities to form social relationships. Inter-and intrapersonal understanding of social norms have been examined separately in ASD adults, showing mixed findings (Baez et al, 2012;Gleichgerrcht et al, 2013;Lehnhardt et al, 2011;Thi ebaut et al, 2016;Zalla et al, 2009). To our knowledge, there is currently no clinical test of inter-and intrapersonal understanding of social norms within the same test.…”
mentioning
confidence: 99%
“…It is intended as a test of appreciation of social norms and the perspectives of other people. Thiebaut et al. (2016) showed that ASD participants will detect faux pas where they are depicted almost as well as TDs.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate whether there is a potential link between repetitive behaviours and abilities associated with social cognition in the ASD participants, we administered the Cartoon Faux Pas Test (CFPT) developed by Thiebaut et al. (2016) .…”
Section: Resultsmentioning
confidence: 99%
“…El Test de los Ojos, a diferencia de los anteriores, no se basa en contextos sociales, sino que la atribución del estado mental o emocional debe hacerse a una imagen del contorno de los ojos de un rostro humano, siendo la identificación la interpretación de la expresión de esa mirada la que se asume como indicador de ToM. Se toma como Teoría de la Mente avanzada porque solo se cuenta con la información del contorno de los ojos y las atribuciones que se hacen no son solo emociones sino estados mentales e intenciones como por ejemplo, "ganas de jugar", "pensativo" o "satisfecho" ( Barón-Cohen, et al, 1997;Sprung, 2010), siendo esta su principal diferencia con los test de reconocimiento emocional, los cuales están centrados en que el sujeto identifique la expresión de una emoción, dejando de lado deseos, intenciones o estados mentales.…”
Section: Introductionunclassified